(untitled) (TAMADDUN NURI JURNALI, 2025)
The article examines the impact of digital education on human cognitive abilities such as memory, attention, and thinking. The results of a study conducted among students who studied using digital technologies and traditional methods are presented. The advantages of digital education, including the development of short-term memory and creative thinking, as well as its disadvantages, such as decreased long-term memory and concentration, are revealed. The conclusion is made about the need for a balanced use of digital and traditional approaches to improve the effectiveness of learning.